Relating Corroded Seven-Strand, Posttensioned Cable Cross-Sectional Properties to Load Capacity - Richard Haskins; Barry White; Robert Ebeling; James Evans (Journal of Engineering)
Multistrand anchors have seen widespread use, providing strength and stability at hydraulic Corps facilities. However, these steel tendons are subject to strength reduction as an effect of corrosion. Methods for evaluating the corroded cable strength do not exist to accurately estimate the time until tendon cables would have to be replaced (at great expense). The following five research tasks are used to address this deficiency: laboratory accelerated corrosion; pull-tests on pristine and laboratory corroded cables; optical scanning; data collection correlated with cross-sectional properties of cables; and development of a method to relate this data to the field. The pull-tests provide measured capacities for seven-strand, posttensioned (PT) cables. An optical scan of the corroded cables provides cross-sectional properties of individual wires within the pulled cables. Trendlines are established for the related peak cable capacities and cross-sectional properties in an effort to determine their correlations. Trendlines for minimum wire area and second-moment short axis diameter are found with low error, making them good predictors of loaded cable capacity. This pull-test dataset has been related back to cable failure in the field, assuming a linear rate of corrosion loss for the cross-sectional properties and required PT capacity.